Jawapan

  • Pengguna Brainly
2016-01-17T17:08:53+08:00
A) f(x) = 3x - 1
     f^2(x) = ff(x)
                = f ( f (x) )
                = f ( 3x - 1 )
                = 3 ( 3x - 1 ) - 1
                = 9x - 3 - 1
                = 9x - 4

B) g(x) = ( x - 1 ) / ( x + 2 )
     g^2(x) = gg(x)
                = g ( x - 1 / x + 2 )
                = ( x - 1 / x + 2 ) - 1 / ( x - 1 / x + 2 ) + 2
                = ( x - 1 - x - 2 ) / ( x - 1 + 2x + 4 )
                = - 3 / ( 3x + 3 )
                = - 1 / ( x + 3 )
2 4 2